2022
DOI: 10.1186/s13020-022-00615-6
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA Miat contributes to the protective effect of electroacupuncture against myocardial fibrosis

Abstract: Background Myocardial fibrosis changes the structure of myocardium, leads to cardiac dysfunction and induces arrhythmia and cardiac ischemia, threatening patients’ lives. Electroacupuncture at PC6 (Neiguan) was previously found to inhibit myocardial fibrosis. Long non-coding RNAs (lncRNAs) play a variety of regulatory functions in myocardial fibrosis, but whether electroacupuncture can inhibit myocardial fibrosis by regulating lncRNA has rarely been reported. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Except for miR-206, the other six myomiRs, miR-1, miR-133a, miR-133b, miR-208a, miR-208b, and miR-499, can be expressed in cardiac muscles. Moreover, multiple studies have demonstrated that these myomiRs are involved in the development of different types of heart diseases, including dilated cardiomyopathy ( 33 ), coronary artery disease ( 34 ), cardiac hypertrophy ( 35 , 36 ), and myocardial fibrosis ( 37 , 38 ). Although miR-208a and miR-208b were not remarkably higher in the sera of cardiac involvement patients, we believe this may suggest that miR-1, miR-133a, miR-133b, and miR-499 are more sensitive to cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Except for miR-206, the other six myomiRs, miR-1, miR-133a, miR-133b, miR-208a, miR-208b, and miR-499, can be expressed in cardiac muscles. Moreover, multiple studies have demonstrated that these myomiRs are involved in the development of different types of heart diseases, including dilated cardiomyopathy ( 33 ), coronary artery disease ( 34 ), cardiac hypertrophy ( 35 , 36 ), and myocardial fibrosis ( 37 , 38 ). Although miR-208a and miR-208b were not remarkably higher in the sera of cardiac involvement patients, we believe this may suggest that miR-1, miR-133a, miR-133b, and miR-499 are more sensitive to cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%